ミナミ ヤマト ヌナターク グン ト カブトダケ ノ チケイ セッピョウ チョウサ ホウコク - 横山, 宏太郎; ヨコヤマ, コウタロウ; YOKOYAMA, Kotaro (国立極地研究所, 1976)
P(論文) 第14次日本南極地域観測隊(1973-1974)のやまと山脈旅行隊は,以前からやまと山脈南西方に望見されていたヌナターク群を調査する支隊を編成した.この支隊は1973年12月13日から18日まで行動し,やまと山脈南西約30 km付近に7個のヌナタークを確認し,露岩上での天文測量(1点)および地形,雪氷,地質の調査を行った.これらのヌナタークのうち北北西に孤立する一峰はかぶと岳,他の六峰より成る山群は南やまとヌナターク群,天側点はくらかけ山,最高峰はくわがた山と命名された.天測によるくらかけ山の位置は72°00'30"S,35°13'30″Eである.ヌナクークの標高は1,986mから2,282 m, 氷床表面との比高はいずれも100 m から150 m 程度である.またこの地域において,深い溝を持つ氷の丘が南東から北西に連なっていることが確認された.その方向はこの地域の氷床の流動方向にほぼ一致すると思われる. A group of six nunataks and an isolated nunatak in the south-west of the Yamato Mountains were explored for the first time in December 1973 by the 14th Japanese Antarctic Research Expedition (1973-1974). The former has been named as the Minami-Yamato Nunataks, and the latter as the Kabuto Nunatak. The main group of the Minami-Yamato Nunataks lying NNW-SSE is composed of five nunataks about 30 km SW from the south end of the Yamato Mountains, and one nunatak is located about 7 km E of the main group. The astro-fixed position of the Kurakake Nunatak in the main group determined is 72°00'30"S, 35°13'30"E. The Kabuto Nunatak is about 20km NNW, isolated from the main group. The elevation of the nunataks are 1,968m to 2,282m above sea level and the surface elevation of the ice sheet is about 1,850m to 2,100m. Between the Yamato Mountains and these nunataks, two trains of ice hills run from NW to SE, which presumably coincides with the general direction of the flow of the ice sheet. departmental bulletin paper